Maturational timing and swim performance in collegiate female swimmers. Manuscript and coaching applications - Cornett, A. C.; Wagner, S.; Duski, A.; Wright, B. V.; Stager, J. M. (Journal of Swimming Research, 2017)
The purpose of this study was to determine if maturational timing is related to collegiate swim performance. Maturational timing was estimated using age at menarche (AaM), which was determined retrospectively in collegiate swimmers (N = 273). Each swimmer`s best performance during the 2015-2016 NCAA season was obtained from the USA Swimming database and selected based on Power Point Score (PPS), a standardized score given to all performances in the database. Independent samples t tests were used to compare (i) PPS and body mass index (BMI; from selfreported height and weight) between earlier maturing (youngest 33% at menarche) and later maturing (oldest 33% at menarche) swimmers and (ii) AaM and BMI between lower performing (lowest 33% of PPS) and higher-performing (highest 33% of PPS) swimmers. The later maturers performed better than the earlier maturers (PPS 801.7 vs. 759.8, t = 2.10, P = 0.04, d = 0.33) and had lower BMIs (22.5 vs. 23.3 kg/m2, t = 2.41, P = 0.02, d = 0.36). The higher-performing swimmers were later maturers than the lower-performing swimmers (AaM 14.0 vs. 13.4 years, t = 2.87, P = 0.01, d = 0.45) and had lower BMIs (22.5 vs. 23.2 kg/m2, t = 1.97, P = 0.05, d = 0.31). These findings suggest that the relationship between maturational timing and swim performance may be due, at least in part, to physical traits common to both later maturers and better performers.